What is a real effectiveness of the behavioral counseling to promote a healthy lifestyle? - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Short description of behavioral counseling and its effectiveness in prevention of cardiometabolic diseases.